Differentiating Online Posting Behaviors of Violent and Nonviolent Right-Wing Extremists. (December 2022) - Scrivens, Ryan; Wojciechowski, Thomas W.; Freilich, Joshua D.; Chermak, Steven M.; Frank, Richard
There is an ongoing need for researchers, practitioners, and policymakers to detect and assess online posting behaviors of violent extremists prior to their engagement in violence offline, but little is empirically known about their online behaviors generally or the differences in their behaviors compared with nonviolent extremists who share similar ideological beliefs particularly. In this study, we drew from a unique sample of violent and nonviolent right-wing extremists to compare their posting behaviors in the largest White supremacy web-forum. We used logistic regression and sensitivity analysis to explore how users' time of entry into the lifespan of an extremist sub-forum and their cumulative posting activity predicted their violence status. We found a number of significant differences in the posting behaviors of violent and nonviolent extremists which may inform future risk factor frameworks used by law enforcement and intelligence agencies to identify credible threats online.